Studentsâ Conception About The Period Of A Simple Pendulum - *, Pujayanto (Sebelas Maret University, 2016)
This study aims to describe the studentsâ conception of Physics Education Study Program,Â Teacher Training and Education Faculty, Sebelas Maret University, about the concept of a simple pendulum period, after conducting a basic physics experiment. A simple pendulum consists of a mass (m) that is hanging at the end of a light string. The string is considered ideal, which is massless and can not be stretched. In the laboratory, students investigated the affects of a few different physical variables on the period of a simple pendulum (T). The variables were mass (m), length of the pendulum (L), and the initial angular displacement (Î¸). The results of the study showed that: 1). all students had a right conception about the dependency of a simple pendulum period on the string length, that is, the period of a simple pendulum is proportional to the square root of the string length; 2). all students had a right conception about the dependency of a simple pendulum period on the mass, that is, the period of a simple pendulum is not dependent on the mass; 3). 42% of the students had a wrong conception about the dependency of the period of a simple pendulum on the initial angular displacement, which they concluded that the initial angular displacement Â does not affect the period of a simple pendulum. It is, analytically provable that the period of a simple pendulum depends on the initial angular displacement.Â